Penerapan Green Computing pada E-Learning Di Universitas Serelo Lahat - Al Hakim, Muhammad Ilham; Damayanti, Selvia (Universitas Multi Data Palembang, 2025)
Green Computing is a program based on an environmentally friendly concept that emphasizes the efficient use and management of computer technology, devices, and infrastructure by reducing excessive consumption and minimizing environmental waste. Serelo Lahat University (Unsela) is an institution that has gradually integrated Green Computing into its educational processes.The objective of this study is to describe the use of e-learning as an online learning method that supports the Green Computing concept and reduces paper consumption. The data collection methods employed include literature reviews, interviews, and observations. Data analysis is conducted using the Green Computing framework, which encompasses the concepts of green design, green use, strategies and policies, and green disposal.The analysis findings indicate that Unsela has implemented Green Design in its IT infrastructure, particularly with the establishment of a data center. Green Use is evident in the application of e-learning, where all learning and administrative processes are carried out digitally. Green Strategies and Policies are reflected in the top leadership of Unsela, who have established policies to reduce electricity consumption. Green Disposal is demonstrated through the practice of reusing hardware. In conclusion, it can be stated that Unsela has successfully implemented the Green Computing concept across all aspects.